Chapter 7 - Ethnobotany of Andean root crops: tradition and innovation—Arracacha (Arracacia xanthorrhiza Bancr.), Yacón (Smallanthus sonchifolius (Poepp.) H. Rob.), Mauka (Mirabilis expansa (Ruíz & Pav.) Standl.), Ahipa (Pachyrhizus ahipa Parodi), Maca (Lepidium meyenii Walp.), Achira (Canna indica L.) - Luziatelli, G.; Alandia, G.; Rodríguez, J.P.; Manrique, I.; Jacobsen, K.; Sørensen, M. (Elsevier, 2023)
Andean root crops encompass six species domesticated and cultivated since ancient times for their edible underground parts in the Andean region. Once considered neglected or only maintained in the rural areas, two of them have recently made an incursion into the global market for nutraceuticals and functional foods. However, the rest are still little known, and some are possibly endangered by extinction. This review reports on traditional uses made of these crops as well as the latest evidence available on their beneficial properties, complemented with field observations of the crops and their uses in Peru, Colombia, and Bolivia.